Kinematic and Dynamic Study of the Rotary Crusher Transmission Gear in the Potato Digger - Tarverdyan, A. P.; Hayrapetyan, H. H. (ՀԱԱՀ հիմնադրամ)
Theoretical study of the geometric and kinematic as well as dynamic parameters of the gear drive wheel rotary soil crusher of the potato digger with planetary mechanism has been implemented and the optimal parameters have been selected. In the result of field and laboratory experiments it has been revealed that the distance between the grouser bars of the drive gear wheel should be approximately 0.17 m, thus, the angle formed by the adjacent grouser bars makes 180, while their number should be 20.
Keywords: Agricultural Engineering